Pembelajaran Berparadigma Konstruktivistik: Mengembangkan Standar Kompetensi Lulusan Program Magister Pendidikan Agama Islam Pascasarjana IAIN Madura - Siswanto, Siswanto (TADRIS: Jurnal Pendidikan Islam, 2018)
Abstract: There are four focuses in this study, namely the understanding of lecturers and students about the formulation of graduate competency standards (SKL) of PAI programme of Postgraduate IAIN Madura, development strategies using constructivist paradigm approaches, and learning and evaluation models developed by this programme. By using a qualitative approach, this study finds: firstly, Graduate competency standards formulation according to the understanding of lecturers and students are relevant to the expectations of graduate users. Determination of this formula is adjusted to the regulations governing higher education quality standards. Secondly, The development strategies are carried out by developing lecture materials based on Indonesian national qualification framework, increasing the competence of lecturers and students through education and training, developing the tradition of research and community enggagement programs for students. Thirdly, The learning model is developed with contextual learning, problem-based learning, inquiry learning, which is manifested in classroom seminars, independent learning, writing papers, presentations and dialogues. Evaluation includes two types, namely process evaluation and outcome one. Â Keywords: Graduates competency standards, learning, constructivistic paradigm, Islamic religiuos education Â Abstrak: Terdapat empat fokus dalam penelitian ini, yaitu pemahaman dosen dan mahasiswa tentang rumusan standar kompetensi lulusan (SKL) Progam Magister PAI Pascasarjana IAIN Madura, strategi pengembangannya dengan menggunakan pendekatan paradigma konstrukstivistik, serta model pembelajaran dan evaluasi yang dikembangkan. Dengan menggunakan pendekatan kualitatif, maka penelitian ini menghasilkan: Pertama, Rumusan SKL menurut pemahaman dosen dan mahasiswa relevan dengan ekspektasi pengguna lulusan. Penetapan rumusan ini disesuaikan dengan regulasi yang mengatur tentang standar mutu pendidikan tinggi. Kedua, strategi pengembangannya dilakukan dengan mengembangkan materi perkuliahan berbasis KKNI, meningkatkan kompetensi dosen dan mahasiswa melalui pendidikan dan pelatihan, mengembangkan tradisi riset dan program pengabdian masyarakat bagi mahasiswa. Ketiga, model pembelajaran yang dikembangkan adalah pembelajaran kontekstual, pembelajaran berbasis masalah, inquiry learning, yang dimanifestasikan dalam kegiatan seminar kelas, independent learning, paper writing, presentasi dan dialog. Evaluasi meliputi dua jenis evaluasi, yaitu evaluasi proses dan evaluasi hasil. Â Kata kunci: Pembelajaran, Paradigma Konstruktivistik, Standar Kompetensi Lulusan, Pendidikan Agama Islam